Gond, the Aboriginal - Tomar, M. S. (Indian Forester, 1958)
The article describes the social life of Gonds such as religion, marriage, disposal of the dead, etc. Lastly it summarizes the importance of Gond as a forest labour. This study is mainly confined to the Bori Range of Hoshangabad Division, Madhya Pradesh.